"What's going on" in Ferguson? Online news frames of protest at the police killing of Michael Brown. (September 2020) - Riddle, Travis A.; Turetsky, Kate M.; Bottesini, Julia G.; Wayne Leach, Colin
Public reactions to protests are often divided, with some viewing the protest as a legitimate response to injustice and others perceiving the protest as illegitimate. We examine how online news sources oriented to different audiences frame protest, potentially encouraging these divergent reactions. We focus on online news coverage following the 2014 police shooting of a Black teenager, Michael Brown. Preregistered analyses of headlines and images and their captions showed that sources oriented toward African Americans were more likely to include content conveying racial injustice and legitimacy of the subsequent protests than sources oriented toward a general audience. In contrast, general audience sources emphasized conflict between protesters and police, making fewer references to the protesters' cause. Whereas much work on media segregation addresses the propensity of audiences to consume different sources, our work suggests that news sources may also contribute to information fragmentation by differentially framing the same events.